Problem-Based Learning for Enhancing Learning Motivation in Elementary Science and Social Studies - Nur Zam-zam; Sarintan N Kaharu; Pahriadi Pahriadi; Azizah Azizah; Putriwanti Putriwanti (Equator Science Journal, 2026)
Students' learning motivation in Science and Social Studies (IPAS) at SD Inpres 8 Mamboro was relatively low, as reflected in their limited participation and enthusiasm during classroom learning activities. Therefore, this study aimed to examine the effect of Problem-Based Learning (PBL) on students' learning motivation in IPAS. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 26 students in the experimental group and 25 students in the control group. Data were collected using a learning motivation questionnaire based on six indicators: perseverance, resilience in facing difficulties, interest in problem-solving, independence, preference for challenges, and strong determination. The data were analyzed using descriptive statistics and an Independent Samples t-test. The results showed that the post-test mean learning motivation score of the experimental group (M = 61.73, SD = 2.71) was substantially higher than that of the control group (M = 37.76, SD = 2.91). Hypothesis testing revealed a statistically significant difference between the two groups (t(49) = 30.503, p < .001). Furthermore, the effect size analysis yielded a Cohen's d value of 8.544, indicating a very large effect. These findings demonstrate that Problem-Based Learning (PBL) is an effective instructional approach for enhancing students' learning motivation by providing meaningful, contextual learning experiences that actively engage students in IPAS.